Negative regulation of RTKs: receptor ubiquitylation, endocytosis and feedback loops - Yarden, Yosef (Henry Stewart Talks, 2007)
Signal transduction by growth factor-activated protein tyrosine kinase receptors, Receptor endocytosis, The three vesicular sorting steps occurring at the plasma membrane, in endosomes and in a pre-lysosomal compartment, The emerging role of mono-ubiquitin and ubiquitin-binding proteins in sorting of active receptors to degradation
Archived at 2018/05/31